Multiservice home gateways business model, execution environment, management infrastructure. - Royon, Yvan; Frenot, Stephane
The home gateway market is undergoing deep changes. On one side, home networks are evolving, getting dynamic and federating more and more devices. On the WAN side, new actors appear, such as multimedia content providers. From both sides emerge new features and new management needs. In this article we highlight challenges and benefits of moving more intelligence to the home gateway, making it more than a simple interconnection device. We argue that we need a full-fledged execution environment on gateways to address the evolution of business models. We present this evolution and summarize existing solutions for execution environments and management for home gateways. Then we propose two improvements that reflect the new requirements. The first improvement is a high-level virtualization of service gateways, and the second one recommends an end-to-end dynamic multiprovider management system.
Keywords: Business model; Execution environment; Home networks; Management infrastructure; Multimedia content providers; Multiprovider management; Multiservice home gateways; Service gateways; Wide area networks